2020
DOI: 10.1186/s12978-020-00912-z
|View full text |Cite
|
Sign up to set email alerts
|

Causal mechanisms of postnatal depression among women in Gondar town, Ethiopia: application of a stress-process model with generalized structural equation modeling

Abstract: Background Postnatal depression (PND) is the second most common cause of disability and the most common complication after childbirth. Understanding the potential mechanisms by which the stress process can lead to PND is an important step for planning preventive interventions for PND. This study employed a stress process model to explore the possible pathways leading to PND in Gondar Town, Ethiopia. Methods A community-based cohort study was conduc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 24 publications
(23 citation statements)
references
References 78 publications
6
17
0
Order By: Relevance
“…Although 12.5% of women reported experiencing a probable CMDs at baseline, only 7% experienced CMD at the follow-up data collection time-point. Similar prevalence estimates have been reported in studies on postnatal CMDs from Ethiopia (53) and Zimbabwe (54) where the prevalence ranged between 9% and 34%. The low prevalence of CMDs at baseline and follow-up is likely because the majority of women were in the third trimester of pregnancy or had already given birth, as studies have found that mild to moderate symptoms of depression improve during the last trimester of pregnancy and after birth (20,55) , and that the prevalence of depression is higher during pregnancy compared to after childbirth (56) .…”
Section: Discussionsupporting
confidence: 85%
“…Although 12.5% of women reported experiencing a probable CMDs at baseline, only 7% experienced CMD at the follow-up data collection time-point. Similar prevalence estimates have been reported in studies on postnatal CMDs from Ethiopia (53) and Zimbabwe (54) where the prevalence ranged between 9% and 34%. The low prevalence of CMDs at baseline and follow-up is likely because the majority of women were in the third trimester of pregnancy or had already given birth, as studies have found that mild to moderate symptoms of depression improve during the last trimester of pregnancy and after birth (20,55) , and that the prevalence of depression is higher during pregnancy compared to after childbirth (56) .…”
Section: Discussionsupporting
confidence: 85%
“…This stress model has been widely used in the study of mental illness (Dadi et al . 2020 ). Previous studies have used this theory to explore mediating factors and develop interventions to effectively optimize responses to stress (Crum et al .…”
Section: Introductionmentioning
confidence: 99%
“…Perinatal depression refers to depression occurring during pregnancy (antenatal depression) and after child birth (postnatal depression) [ 5 ]. In Ethiopia, the prevalence of antenatal and postnatal depression has been reported in the range from 7 to 31.1% and 9 to 33.8%, respectively [ 6 9 ].…”
Section: Introductionmentioning
confidence: 99%